A Retrospective Study of 52 Patients With Primary Small Cell Carcinoma of the Esophagus Treated With Radical Surgery. (21st June 2021) - Fan, Ningbo; Wang, Zhen; Huang, Yuanheng; Tan, Zihui; Yang, Han; Lin, Peng
Background: Primary small cell carcinoma of the esophagus (SCCE) is a rare and extremely fatal disease. We aim to evaluate the efficacy of radical surgery for resectable SCCE and to explore potential prognostic factors. Methods: We retrospectively reviewed 52 consecutive SCCE patients who underwent radical surgery from February 1993 to November 2014 at a single institution. The Kaplan-Meier estimator with log-rank test was used to assess overall survival (OS), disease-free survival (DFS) and median survival time. Univariate and multivariable analyses were used to evaluate prognostic factors through Cox proportional hazard regression model. Results: Twenty-five (48.1%) patients were treated with surgery alone, whereas 27 (51.9%) patients underwent adjuvant therapy after surgery. The median OS time was 17.4 months (95% CI: 13.5-21.3). The median DFS time was 13.4 months (95% CI: 7.7-19.0). Patients whose tumors were located in the lower part of thoracic esophagus and the esophagogastric junction showed significantly better OS (27.0 vs. 13.2 months, P = 0.016) and DFS (27.0 vs. 11.3 months, P = 0.017) than those located in the upper and middle parts. Patients with N0 status experienced significantly better OS (21.4 vs. 11.6 months, P = 0.012) and DFS (21.4 vs. 8.6 months, P = 0.012) than those with N+ status. Patients whose tumor lengths were shorter than 5 cm had a better OS (17.4 vs. 5.7 months, P = 0.035) than those longer than 5 cm. Patients who underwent chemotherapy experienced a significantly improved OS (21.0 vs. 14.1 months, P = 0.032) compared to surgery alone. Multivariable analysis showed that lower tumor location, shorter tumor length, pN0 status and chemotherapy independently predicted better OS; lower tumor location and pN0 status independently predicted better DFS. Conclusions: Radical surgery in combination with chemotherapy has better outcomes than surgery alone for resectable SCCE. Higher tumor location, longer tumor length, lymph node metastasis and not undergoing chemotherapy independently predict worse prognoses.